2013
DOI: 10.1017/s001447971300063x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SOIL DRYING ON RATE OF STRESS DEVELOPMENT, LEAF GAS EXCHANGE AND PROLINE ACCUMULATION IN ROBUSTA COFFEE (COFFEA CANEPHORAPIERRE EX FROEHNER) CLONES

Abstract: SUMMARYSeasonal drought stresses as a result of changes in global climate and local weather conditions are among the major factors adversely affecting growth and productivity of Robusta coffee (Coffea canephora pierre ex froehner) in many areas producing the crop. It is believed that there exists a wide range of genetic variability among Robusta coffee clones for traits associated with drought tolerance. Therefore, in an attempt to determine differences among Robusta coffee clones for some growth, physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…However they concur with Effendy et al (2013) as some clones like C20, C1 and C8 exhibited high grafting success using budding compared to top grafting. These results are similar with those of Tesfaye et al (2014) who found that in coffee, the grafting techniques influences vegetative growth parameters and can be used as a criterion to screen precocity materials. Most clones exhibited high grafting success when top grafting was used and it was proposed therefore in this study that this should be adopted for grafting the elite cocoa clones in the study areas.…”
Section: Effect Of Grafting Technique On Selected Growth Parameters Isupporting
confidence: 90%
“…However they concur with Effendy et al (2013) as some clones like C20, C1 and C8 exhibited high grafting success using budding compared to top grafting. These results are similar with those of Tesfaye et al (2014) who found that in coffee, the grafting techniques influences vegetative growth parameters and can be used as a criterion to screen precocity materials. Most clones exhibited high grafting success when top grafting was used and it was proposed therefore in this study that this should be adopted for grafting the elite cocoa clones in the study areas.…”
Section: Effect Of Grafting Technique On Selected Growth Parameters Isupporting
confidence: 90%
“…Interesting variability for WUE was already published for potato [47] coffee [48], and poplar clones [49]. Even though is not matter of this work to identify the genetic basis of such variability, it seems now affordable to do it in near future.…”
Section: Discussionmentioning
confidence: 97%
“…Clones IC-6 and IC-3 are drought tolerant than other clones due to higher proline accumulation (Table 1), the drought tolerant mechanisms could be linked to osmotic adjustment due to more accumulation of proline. In Figure 5 leaf proline concentration of all the clones decreased when the plants were re-watered (Tesfaye et al, 2014). Tesfaye et al (2014).…”
Section: Proline Accumulation On Coffee Under Drought Conditionsmentioning
confidence: 97%
“…In Figure 5 leaf proline concentration of all the clones decreased when the plants were re-watered (Tesfaye et al, 2014). Tesfaye et al (2014).…”
Section: Proline Accumulation On Coffee Under Drought Conditionsmentioning
confidence: 97%
See 1 more Smart Citation